Realization Of Methods Of Comparison Of Sets By Using Relational Dbms Methods - Fedorchenko, K.A. (Journal of Information Technologies in Education (ITE), 2009)
The article deals with questions concerning usage of modern DBMS, such as building queries with the "Great Divide" relational division. Various variants of relational division usage are described. The article contains description of the expressions relational based on algebra as well as examples in SQL language.